Pupil-athletes` learning dispositions and their potential effects in school sports-situated talent development programs - Renström, A.; Stenling, C. (Journal of Athlete Development and Experience, 2019)
There is a worldwide increase in efforts to support talents` development towards elite athletes. The focus of the study was the learning processes among athletes that facilitate this development. Drawing on the learning dispositions concept (Carr & Claxton, 2002), the aim was to create knowledge on the prevalence and possible consequences of variability in learning patterns among pupils enrolled in Nationell Idrottsutbildning Fotboll (NIUF)—a highly selective soccer talent development programme within upper secondary schools in Sweden. In-depth semi-structured interviews were carried out with a total of 13 pupils in their first or second year of NIUF. The data analysis benefited from iterative movement between the data and key learning dispositions: resilience, reciprocity, and playfulness. The findings show a variation in the strength of these dispositions between pupils, particularly with regard to the reciprocity and playfulness dispositions. We propose that individuals who display a comparably stronger manifestation of learning dispositions are better equipped to benefit from the learning opportunities of such programmes. This implies that there is a key role for coaches/educators to play in constructing an environment in which participants may `learn to learn`.